Comportamientos disruptivos en estudiantes de educación básica, un enfoque sistémico. - Ibarra Rodríguez, Yulen Haydemar (2025)
This research was developed in response to the problem of disruptive behaviors in the classroom, which affect the school climate, the teaching-learning process, and coexistence. The general objective was to develop a system of psychopedagogical activities based on the systemic approach to address these behaviors in a basic education student. A qualitative methodology with a single case study design was adopted, applying participant observation techniques and semi-structured interviews with the legal guardian, the teacher, and the student from an educational institution in Quevedo. The results identified disruptive behaviors such as aggression, disobedience, and pedagogical disconnection, associated with complex family dynamics, an unprocessed grief due to the loss of the mother, and unclear boundaries at home. A system of activities aimed at the student, family, and teacher was designed and implemented, based on the principles of systemic pedagogy (belonging, hierarchy, and balance). The implementation revealed resistance from the family system and the student's internalization of a negative identity. It was concluded that the systemic approach is crucial for understanding the multifactorial root of disruption, transcending mere behavioral correction and proposing comprehensive interventions that reestablish order and bonds within the educational-family system.